What Does the Gathering of Israel Mean to Descendants of Joseph in New Zealand? - Thompson, Keith (International journal for the study of new religions, 2022)
The Church of Jesus Christ of Latter-day Saints in New Zealand (variously described hereafter as "the Church," "the LDS Church," "Latter-day Saints" and adjectivally as "LDS") was a small European institution from its inception in the 1850s until the indigenous Maori peoples began to join in large numbers between 1882 and 1895. Those converts completely changed the Church and outnumbered the European membership ten to one by the end of the nineteenth century. That change in the character of the Church’s membership has been studied as a sociological phenomenon, but subjective explanations - how the Church explains that massive growth - have not received detailed consideration. This article therefore involves hermeneutic treatment. It notes the previous sociological analysis, but explains where the indigenous Maori people fit into the theology of the LDS Church. While it recognizes that the authenticity of the Book of Mormon remains a "hotly contested" topic, this article does not engage in that contest. The point of this article is to understand the relevant LDS theology from the inside out.